Pengaruh Pemberian Hormon Medroxy Progesterone Acetat terhadap Ketebalan Endometrium Rattus Norvegicus Betina Strain Wistar - Defi Yulita; M Biomed (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Based on the National Population and Family Planning Agency (BKKBN) data in 2013, there were 8,500,247 couples of childbearing age who were new KB (family planning) participants with the total number using injection was 4,128,115 (48.56%). Research Objectives to find out The Effect of The Administration OF Medroxy Progesterone Acetate Hormone to Endometrial Thickness of The Female Rattus Norvegicus Wistar Strain. The design of this research is the post test only control group design by having  white rats species Rattus Norvegicus Wistar Strain as the poplulation, the samples are taken randomly from all populations that met the following sample criteria: female rats, Aged 12-14 weeks, having body weight of 150 - 200 grams. Based on the calculation of the sample size, the sample size / number of animals r = 10 rats was obtained, with a total sample size for both groups of treatment and control were 20 female rats which included: group 1 amounted to 10 rats that were not given Medroxy Progesterone Acetat hormones as a control group where group 2 amounted to 10 rats which given Medroxy Progesterone Acetat as a treatment group. The results showed the average endometrial thickness in the (P1) Medroxy Progesterone Acetate Hormone group was 493.17 µm ± 114.96, this result was lower than the control group 1192.56 µm ± 428.94. From the ANOVA test table, the P value <0.05 means that there is a very significant difference in the average endometrial thickness between the control group and the treatment group. Based on the results of the Post Hoc Bonfferoni Test, it can be seen that the average endometrial thickness between Control and P1 showed a significant difference (P <0.05). The analysis of the result and discussion of the research can be concluded that: the Medroxy Progesterone Acetate hormone affects the endometrial thickness, and there is a difference in the histological picture of endometrial thickness due to the administration of the Medroxy Progesterone Acetate hormone and without the administration of to the administration of the Medroxy Progesterone Acetate hormone.